2011
DOI: 10.4209/aaqr.2010.11.0098
|View full text |Cite
|
Sign up to set email alerts
|

Fate and Distribution of Polychlorinated Dibenzo-p-dioxins and Dibenzofurans in a Woodchip-fuelled Boiler

Abstract: As yet, very little is known about the PCDD/F fate and distribution in the woodchip-fuelled boilers. In this study, the feeding woodchips, stack flue gases and the ashes in different units of a woodchip-fuelled boiler are sampled to investigate their PCDD/F characteristics. The PCDD/F contents in the bottom residues and fly ashes ranged from 18.9 to 66.3 ng I-TEQ/kg, which are below the Taiwanese PCDD/F regulation for reutilization of bottom residues, but still higher than PCDD/F limitations on soils for agric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 54 publications
0
15
0
Order By: Relevance
“…In the study of PCDD/F output/input ratio related to power plants and boilers, Zhang et al (2013) found out that PCDD/Fs were destroyed during co-combustion of coal and sewage sludge, since the PCDD/F inputs were in the range of 1.17-4.69 µg I-TEQ tonne-MF . On the other hand, Chen et al (2011b) found out that the output PCDD/Fs toxicity was about 7 times greater than that contained in the input woodchip feedstock, indicating that PCDD/Fs were formed in the woodchip-fueled boilers rather than destroyed. The formations of PCDD/Fs in the boilers may be as a result of lower efficiency on combustion and heat exchange system, which may increase retention time of flue gases at PCDD/F de novo formation window.…”
Section: Pcdd/f Emissions From Power/heat Generationmentioning
confidence: 96%
See 1 more Smart Citation
“…In the study of PCDD/F output/input ratio related to power plants and boilers, Zhang et al (2013) found out that PCDD/Fs were destroyed during co-combustion of coal and sewage sludge, since the PCDD/F inputs were in the range of 1.17-4.69 µg I-TEQ tonne-MF . On the other hand, Chen et al (2011b) found out that the output PCDD/Fs toxicity was about 7 times greater than that contained in the input woodchip feedstock, indicating that PCDD/Fs were formed in the woodchip-fueled boilers rather than destroyed. The formations of PCDD/Fs in the boilers may be as a result of lower efficiency on combustion and heat exchange system, which may increase retention time of flue gases at PCDD/F de novo formation window.…”
Section: Pcdd/f Emissions From Power/heat Generationmentioning
confidence: 96%
“…Emissions from this particular woodchip-fueled boiler were compounded by the fact that there were no active control devices for gaseous phase PCDD/Fs. There were about 21.4% of total PCDD/F mass and 18.0% of total PCDD/F toxicity emitted from the stack flue gases of the woodchip-fueled boiler, because only cyclone and bag filter were deployed (Chen et al, 2011b).…”
Section: Pcdd/f Emissions From Power/heat Generationmentioning
confidence: 99%
“…The structural similarity also occurred between PCDD/Fs and PBDEs; similar characteristics were also found, such de novo synthesis (Artha et al, 2011). It is known to us that PCDD/Fs have been found in various sources, such as crematories, sinter plants and so on (Wang et al, 2003a;Wang et al, 2003b;Lee et al, 2004;Lee et al, 2005;Chen et al, 2011;Huang et al, 2011;Lin et al, 2011). PCBs and PCDD/Fs are known to entering soils via dry and wet disposition (Lee et al, 1996), and accumulate in animals (Lee et al, 2009); these are the characteristics PBDEs also possess.…”
Section: Introductionmentioning
confidence: 67%
“…Fax: +886-6-2752484 E-mail address: pjtsai@mail.ncku.edu.tw Chen et al, 2011). Among them, the iron ore sintering process is considered as the most important PCDD/F emission source in many countries (Lahl, 1993(Lahl, , 1994Alcock et al, 1999;Anderson and Fisher, 2002;Aries et al, 2006;Shih et al, 2006Shih et al, , 2008Shih et al, , 2009Chen et al, 2010).…”
Section: Introductionmentioning
confidence: 99%